Design of Pervasive Discovery, Service and Control for Smart Home Appliances: An Integration of Raspberry Pi, UPnP Protocols and Xbee - Sabriansyah Rizqika Akbar; Maystya Tri Handono; Achmad Basuki (Institute of Advanced Engineering and Science, 2017)
Pervasive technology is an important feature in smart home appliances control. With pervasive technology, the user is able to discover and control every device and each service without initialization configuration and setup. Since single-board computer often used in smart home appliances, combining pervasive technology and microcomputer/single-board computer will be important to be applied and make a possibility to create a smart home system based on the requirement of it users that will be beneficial for the smart home users and the developers. This paper proposed a design of pervasive discovery, service, and control system for smart home appliances by integrating Raspberry Pi, UPnP protocols, and Xbee that able to control an RGB LED services such as switching, dimming, change color and read a temperature sensor as an example in smart home appliances. This paper enriched the raspberry Pi GPIO function to be able to control via TCP/IP network with UPnP protocol and receive information from a temperature sensor node via Xbee communication. Service control time is measured with UPnP round trip time by subtracting HTTP response arrival with HTTP request time. GPIO processing time measured at the application level by counting a timer that starts before GPIO process and ended after GPIO successfully executed.